Effect of Ca2+ channel blockers on K+ contractures in twitch fibres of the frog (Rana pipiens). - Gamboa-Aldeco, R (1988)
1. The effects of Ca2+ channel blockers (nifedipine, nitrendipine and diltiazem) were tested on K+ contractures in single muscle fibres of the frog, Rana pipiens. 2. Nifedipine (1 microM) reduced the area under K+ contractures to 24 +/- 9% (4) (100 mM-K+) and 34 +/- 24% (4) (190 mM-K+). Nitrendipine (0.1 microM) reduced the area to 30 +/- 10% (4) (120 mM-K+). The blockade of the contractures was reversible. 3. Diltiazem (1 microM) shortened the first 190 mM-K+ contracture without affecting the peak amplitude. The first contractures, performed at 15-20 min after the removal of diltiazem, were greatly reduced to 29 +/- 14% (4). This effect was reversed after three to five contractures in the absence of the drug. Similar results were obtained with 60 and 100 mM-K+. 4. The resting potential in control saline and after a brief exposure to 120 mM-K+ was not affected by the dihydropyridines and diltiazem. 5. Slow and fast Ca2+ currents were not modified by 1 microM-diltiazem at any stimulation rate or with pre-pulse depolarizations. Diltiazem (50 microM) did not affect the fast Ca2+ current and reduced the slow one to 48 +/- 10% (4). 7. The reduction of K+ contractures by Ca2+ channel blocking agents was not related to a blockade of Ca2+ currents. This can be tentatively explained by interactions of these compounds on membranes sites which regulate the coupling between membrane depolarization and contraction.